An idea of thin-plate thermal mirror I. Mirror created by a heat pulse - Płochocki, Z.; Mioduchowski, A. (Archives of Mechanics, 1997)
An idea and the theory of thermal mirrors created on the surfaces of a simply supported thin plane circular plate of an isotropic thermoelastic solid material by a uniform heat pulse, which is applied to one of the plate surfaces, is presented. Such a thermal mirror is - within the approximations applied for obtaining the solutions of the heat conduction and thermoelasticity equations - an ideal (aberration-free) optical mirror. The optical properties of the thermal mirror and their time evolution are derived and discussed in two asymptotical time regimes: the short-time and the long-time ones. Observability conditions for optical characteristics of the thermal mirror are estimated. Theoretical possibilities of an application of the thermal mirror to experimental determination of the temperature conductivity of a material are discussed. The theory presented can be also used for estimations of distortions of optical properties of pulse high power optical systems, originated by absorption of light by optical mirrors in such systems.